Implementation of Civil Servant Control Functions at the Mulak Seframe Subdistrict Office, Lahat Regency: Implementasi Fungsi Pengendalian Pegawai Negeri Sipil Pada Kantor Camat Mulak Sebingkai Kabupaten Lahat - Pidia, Anis; Apriani, Ike (Gayaku Publisher, 2023)
This research was conducted at the Mulak Seframe Subdistrict Office, Lahat Regency. The aim of the research is to analyze how the Civil Servant Control Function is implemented at the Mulak Seframe Subdistrict Office, Lahat Regency. Data sources are primary data and secondary data. The data collection methods in this research are literature study and field study consisting of observation, interviews and documentation. The existing controls at the Mulak Seframe Subdistrict Office, Lahat Regency, have generally been implemented well, such as: 1). Control of activities to be carried out by employees. The process of controlling activities or work programs has been implemented by determining who will carry out the activity and how the activity will be carried out and where the activity will be carried out. 2). Control over the process of determining the limits of what employees will do by determining the expected results. In this control, employees know the limits of what can be done with the aim of getting results as expected. 3). Control in determining direction so that all activities run according to targets. In this control, employees in carrying out their activities have a direction and goals or targets that have been determined by the leadership. 4). Control in determining the organizational structure and division of tasks for each employee. Employees are given tasks in accordance with their main duties and functions.